Fast and efficient copper-mediated 18F-fluorination of arylstannanes, aryl boronic acids, and aryl boronic esters without azeotropic drying - Salla Orvokki Lahdenpohja; Noora Annika Rajala; Johan Rajander; Anna Kaarina Kirjavainen (Springer Internat. Publ., 2025)
Background
Copper-mediated radiofluorination is a straightforward method to produce a variety of [18F]fluoroarenes and [18F]fluoroheteroarenes. To minimize the number of steps in the production of 18F-labelled radiopharmaceuticals, we have developed a short and efficient azeotropic drying-free 18F-labelling method using copper-mediated fluorination. Our goal was to improve the copper-mediated method to achieve wide substrate scope with good radiochemical yields with short synthesis time.
Results
Solid phase extraction with Cu (OTf)2 in dimethylacetamide is a suitable activation method for [18F]fluoride. Elution efficiency with Cu (OTf)2 is up to 79% and radiochemical yield (RCY) of a variety of model molecules in the crude reaction mixture has reached over 90%. Clinically relevant molecules, norepinephrine transporter tracer [18F]NS12137 and monoamine transporter tracer [18F]CFT were produced with 16.5% RCY in 98 min and 5.3% RCY in 64 min, respectively.
Conclusions
Cu (OTf)2 is a suitable elution agent for releasing [18F]fluoride from an anion exchange cartridge. The method is fast and efficient and the Cu-complex is customizable after the release of [18F]fluoride. Alterations in the [18F]fluoride elution techniques did not have a negative effect on the subsequent labelling reactions. We anticipate this improved [18F]fluoride elution technique to supplant the traditional azeotropic drying of [18F]fluoride in the long run and to concurrently enable the variations of the copper-complex.